DIETARY INFLAMMATORY POTENTIAL AND FOOD PATTERNS IN RELATION TO GUT MICROBIOME AMONG CHILDREN WITH CROHN'S DISEASE: A COMPARATIVE STUDY WITH HEALTHY CONTROLS. (21st January 2021) - Breton, Jessica; Tu, Vincent; Tanes, Ceylan; Quinn, Ryan; Conrad, Maire; Kachelries, Kelly; Bittinger, Kyle; Baldassano, Robert; Compher, Charlene; Albenberg, Lindsey
Abstract: Introduction: The microbiome has been suggested to play an important role in the pathogenesis and progression of Crohn's disease (CD) with the components of a Western diet, in turn, potentially altering the gut microbiome. We conducted an observational study comparing dietary influences on the gut microbiota in children with active or quiescent CD with healthy controls. Method: A prospective cross-sectional study including 58 children with CD (36 with clinically active disease, PCDAI>10) between 6 and 21 years of age and 56 healthy controls was conducted. Dietary intake was estimated using a 3 day dietary recall. The following measurements were selected to assess diet quality based on 1) consumption measured against the American Dietary Guidelines (HEI-2015) (a higher score over 100 representing a healthier diet) and 2) inflammatory potential (DII) (a higher score representing a more pro-inflammatory diet). Compositional and functional analysis of the fecal microbiome was performed using shotgun metagenomics DNA sequencing and associations with dietary indices was modelled with linear mixed-effects models after controlling for confounding effects. Results: Energy and dietary intakes between the healthy and CD cohorts were similar with the exception of fiber intake (%DRI), which was significantly lower in children with active CD than healthy controls (41.4 vs. 50.4, P =0.03). A similarly low total HEI-2015 score was found in patients with active and quiescent CD in comparison to healthy controls respectively (47.6 vs. 51.0 vs. 49.7, P = 0.41). A pro-inflammatory total DII score was found in all three groups (0.48 vs. 0.41 vs. 0.51, P =0.87). At the microbiome level, HEI-2015 ( P =0.009) and DII ( P = 0.024) showed significant positive and negative correlations with alpha-diversity, respectively, in children with quiescent CD only (Figure 1). In children with active CD, Proteobacteria Enterobacteriaceae displayed a significant positive correlation with DII ( P = 0.006) (Figure 2), where a more pro-inflammatory DII score correlated with higher Escherichia coli relative abundances ( P = 0.006). Conclusions: To our knowledge, this is the largest study assessing dietary indices to evaluate the effects of diet quality on the gut microbiome in children with CD. Our results suggest important differential dietary influences on the gut microbiome according to clinical disease status in comparison to healthy children, with low quality diet and higher pro-inflammatory potential being associated with overall lower microbiome diversity in inactive CD and an enrichment in Proteobacteria, specifically E. coli, in children with active CD. Current ongoing functional analyses, including metabolomics, will shed light on the underlying diet-microbiota interactions implicated in CD and potentially assist clinical nutrition guidance and development of new dietary therapeutic trials.